Recensión a "Out of order. Assessing the general theory of crime" (Erich Goode editor). 2008. Stanford, California: Stanford Social Sciences, an imprint of Stanford University Press (270 páginas) - Serrano Maíllo, Alfonso (Revista de Derecho Penal y Criminología, 2019)
-